The Effect of PT Link and Waterbath Antigenic Retrieval Procedures On The Expression of Common Receptors In Breast Cancer Cases - Ahmed Abdelbadie; Elsadig Ahmed Adam; Manar Abdelrahman (Sudan Journal of Medical Sciences)
Background: Antigen retrieval (AR) techniques play a major role in determining the quality and functional state of tissue proteins recovered from formalin fixed paraffin embedded blocks (FFPEB). Different techniques are used each with its merits and drawbacks. Materials and Method: FFPEB from cases diagnosed as breast cancer were examined for the expression of estrogen- receptor (ER), progesterone receptor (PR) and HER2 by immunohistochemical techniques using two different AR methods. Results: Fifty cases, 49 were from females, the age ranged from 28–85 years were examined. The expression of ER using water bath and PT link (pretreatment system) as antigen retrieval methods was equal, both methods showed 20(40%) positive cases and 30(60%) negative cases, whereas, the expression of PR was found positive in 18 cases (36%) and negative in 32 (64%) when water bath was used, in comparison to10 positive (20%) and 40 negative (80%) when PT link was used (P value 0.312).The expression of HER2 was as follows; water bath HER2 weak positive 20 cases (40%), moderate expression 10 cases (20%), overexpression 2 cases (4%). PT link weak expression 13 cases (26%), moderate expression 15 cases (30%), overexpression 4cases (8%); yet, the total number of negative cases and positive cases was equal for both methods (p-value 0.035). Conclusion: Antigen retrieval methods were found to affect the expression of common receptors in breast cancer. The magnitude of this effect was found to be significant in PR and HER2 receptors, however, the different methods of antigen retrieval did not affect the expression of ER. The appropriate and suitable retrieval methods have to be chosen individually for each receptor.